51.3k views
0 votes
Find the product mentally. (2m - 9)2

2m2 - 18m + 81
2m2 - 81m + 81
4m2 - 36m + 81

2 Answers

4 votes
Hi there!

• (a - b)² = a² - 2ab + b²

Simplify with th' following identity :-

(2m - 9)²

⇒ (2m)² - 2 × 2m × 9 + 9²

⇒ 4m² - 36m + 81

Hence,
4m² - 36m + 81 is Correct Option!

~ Hope it helps!

User Stckvrflw
by
4.4k points
5 votes
Hi there!


{(2m - 9)}^(2) =
Remember the following


{(2m - 9)}^(2) = (2m - 9)(2m - 9)
Now we can easily work out the parenthesis using FOIL method.

First 2m × 2m = 4m^2
Outside 2m × -9 = -18m
Inside 2m × -9 = -18m
Last -9 × -9 = 81

Finally some simplifying

(2m - 9)(2m - 9) = \\ 4 {m}^(2) - 18 m - 18m + 81 = \\ 4 {m}^(2) - 36m + 81

The third answer is correct.
~ Hope this helps you!
User Darren Reid
by
4.8k points